Clinicopathologic Associations in a Large International Cohort of Patients With Giant Cell Arteritis. Issue 6 (2nd April 2022) - Putman, Michael S.; Gribbons, K. Bates; Ponte, Cristina; Robson, Joanna; Suppiah, Ravi; Craven, Anthea; Watts, Richard; Luqmani, Raashid; Merkel, Peter A.; Archer, Amy M.; Grayson, Peter C.
Abstract : Objective: In addition to aiding in diagnosis, histopathologic findings from temporal artery biopsy (TAB) specimens in giant cell arteritis (GCA) may be valuable for their associations with clinical features of the disease. This study was undertaken to compare histopathologic findings on TAB with biopsy interpretation and demographic, clinical, and imaging features at time of diagnosis. Methods: Patients with a clinical diagnosis of GCA who had a TAB were selected from an international, multicenter observational cohort of vasculitis. Associations between demographic, clinical, radiographic, and histopathologic features were identified using bivariate testing and multivariate regression modeling. Results: Of 705 patients with GCA who underwent TAB, 69% had histopathologic evidence of definite vasculitis. Specific histopathologic findings included the presence of giant cells (51%), fragmentation of the internal elastic lamina (41%), intimal thickening (33%), and predominantly mononuclear leukocyte infiltration (32%). Histopathologic interpretation of definite vasculitis was independently associated with giant cells (odds ratio [OR] 151.8 [95% confidence interval (95% CI) 60.2–551.6]), predominantly mononuclear leukocyte infiltration (OR 11.8 [95% CI 5.9–24.9]), and fragmentation of the internal elastic lamina (OR 3.7 [95% CI 1.9–7.4]). A halo sign on temporal artery ultrasound and luminal damage of large arteries on angiography were significantly associated with presence of giant cells (OR 2.6 [95% CI 1.1–6.5] and OR 2.4 [95% CI 1.1–5.2], respectively). Specific histopathologic findings were associated with older age, but no associations were identified with vision loss or other clinical features. Conclusion: Histopathologic findings in GCA are strongly associated with the clinical diagnosis of GCA but have a limited role in identifying patterns of disease.